2007
DOI: 10.1111/j.1468-1331.2007.01970.x
|View full text |Cite|
|
Sign up to set email alerts
|

Prescribing patterns of antiepileptic drugs in Italy: a nationwide population‐based study in the years 2000–2005

Abstract: To evaluate prevalence of use and prescribing patterns of antiepileptic drugs (AEDs) in Italian general practice. Primary care data were obtained from the Health Search Database, a longitudinal observational database implemented by the Italian College of General Practitioners (GPs). We selected 465 061 subjects registered by the end of 2005 in the lists of 320 GPs, homogeneously distributed throughout Italy. Prevalence of AED use was assessed in the entire sample and by drug type, age group, year and main geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 17 publications
10
68
0
Order By: Relevance
“…A similar trend of increasing prescription of newer compounds has already been described not only in SE, but more generally in patients with epilepsy and in the general population (6)(7)(8)(9)(10)20). In the present study, this increase was mainly due to levetiracetam and lacosamide.…”
Section: Discussionsupporting
confidence: 57%
“…A similar trend of increasing prescription of newer compounds has already been described not only in SE, but more generally in patients with epilepsy and in the general population (6)(7)(8)(9)(10)20). In the present study, this increase was mainly due to levetiracetam and lacosamide.…”
Section: Discussionsupporting
confidence: 57%
“…Recent increases have been observed in the use of antiepileptics in other elderly populations 21,30 . The prevalence of epilepsy among the elderly is relatively low, varying from 1% to 3% 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unlikely that increases in the incidence and/or prevalence of this condition would explain the increase from 7% to 22% in the use of antiepileptics in the current study. It is more likely that these medications are being used for other therapeutic purposes, such as pain relief, prevention of migraine, management of bipolar disorder, or neurological treatment of patients with a history of stroke 21,30 . In addition, studies in high-income countries 19,20 have shown an increase in the use of psychoactive drugs, both psychoanaleptics and psycholeptics 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The GPs were selected on a geographical basis to include patients representing the distribution of the Italian (mostly adult) population [7]. The information collected includes anonymous data about patient demographics, medical diagnoses coded according to the ninth edition of International Classification of Disease (ICD-9-CM), drug prescriptions coded according to the Anatomical Chemical classification system, hospital referrals, diagnostic investigations with results, and date of death.…”
Section: Methodsmentioning
confidence: 99%